Dragon Masters: Howl of the Wind Dragon - 20 - West, Tracey, 1965-; Howells, Graham (New York, NY : Scholastic Inc., 2021)
The wizard Astrid is planning to cast the False Life spell which will bring to life the bones of giant ancient beasts and allow her to conquer all the kingdoms; in order to prevent her the Dragon Masters must find the Wind Dragon, the final dragon needed to undo the spell--but that dragon and her Dragon Master are captives, and it is up to Drake and his friends to rescue them, and hope they are in time to stop Astrid.
Keywords: Dragons -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Friendship -- Juvenile fiction; Rescues -- Juvenile fiction; Adventure stories; Dragons -- Fiction; Wizards -- Fiction; Magic -- Fiction; Friendship -- Fiction; Rescues -- Fiction; Adventure and adventurers -- Fiction; Children's books